2018
DOI: 10.1136/heartjnl-2018-313876
|View full text |Cite|
|
Sign up to set email alerts
|

Daytime variation of perioperative myocardial injury in non-cardiac surgery and effect on outcome

Abstract: ObjectiveRecently, daytime variation in perioperative myocardial injury (PMI) has been observed in patients undergoing cardiac surgery. We aim at investigating whether daytime variation also occurs in patients undergoing non-cardiac surgery.MethodsIn a prospective diagnostic study, we evaluated the presence of daytime variation in PMI in patients at increased cardiovascular risk undergoing non-cardiac surgery, as well as its possible impact on the incidence of acute myocardial infarction (AMI), and death durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(9 reference statements)
1
9
2
Order By: Relevance
“…These results illustrate the new system can replace EuroSCORE II, and has a higher ability to distinguish high-risk patients. Generally, the risk of operation in AMI patients is higher than of other patients [ 36 ]. Subset analysis found the new system significantly improved the predictive power in the AMI subset.…”
Section: Discussionmentioning
confidence: 99%
“…These results illustrate the new system can replace EuroSCORE II, and has a higher ability to distinguish high-risk patients. Generally, the risk of operation in AMI patients is higher than of other patients [ 36 ]. Subset analysis found the new system significantly improved the predictive power in the AMI subset.…”
Section: Discussionmentioning
confidence: 99%
“…Before the analysis, we defined surgeries in the “morning” period as procedures for which the first incision occurred between 7 a.m. and 12 a.m.; and surgeries in the “afternoon/night” period as procedures for which the first incision occurred between 12:01 p.m. and 6:59 a.m. of the next day. These time intervals reflect the Hospital work shifts of the surgical at our study center and are an example of the pattern of categorization between morning and afternoon surgeries previously described in the literature [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent pilot study including patients submitted to aortic valve replacement assessed whether this time pattern occur after cardiac surgeries, showing that the incidence of major cardiovascular complications in patients undergoing surgery in the afternoon is lower [ 15 ]. Likewise, a cohort study conducted to assess daytime variation in cardiovascular events after non-cardiac surgeries did not find an influence of the time of the surgery on PMI, but the incidence of acute myocardial infarction was higher in the afternoon group [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Montaigne et al did have reported that the incidence of major adverse cardiac events in the afternoon surgery group was significantly lower than that in the morning group [80]. More interestingly, in patients undergoing non-cardiac surgery, Lavallaz et al found that the incidence of AMI during follow-up is instead increased in the afternoon surgeries [81]. Nevertheless, a better understanding of the relationship between circadian clock and cardiovascular disease may help to develop more targeted and personalized treatment strategies for patients.…”
Section: Disruption Of Circadian Bp Rhythm and Cardiovascular Diseasementioning
confidence: 95%